The Carrier Rate of Treponema pallidum (Syphilis) Antibody Among Women in Some Selected Locations in Ondo State, Nigeria. - Fadipe, D.O.1*, Omotuyi, I.O. 2 and Olajubu, F.A. 1 (Sokoto Journal of Medical Laboratory Science)
Syphilis is a multi-stage, vertically (mother to child transmission) or sexually transmitted disease caused by Treponema pallidum. It is an obligate human pathogen renowned for its invasiveness and immune evasiveness. It is of global concern because it causes worldwide health problem like congenital syphilis, neurological conditions such as meningitis, hemiplegia, stroke, aphasia, seizures, and Tabes dorsalis. It does also Gummatous syphilis which features severe skin or visceral lesions called Gummas and as such should be the concern of all public health agencies. This study was done in order to determine the carrier rate of Treponema pallidum among apparently healthy women in Ondo State, Southwest Nigeria. Four hundred volunteered women from the three senatorial districts of the State were screened for the antibody to T. pallidum to determine their sero-positivity percentage. The rapid test kit was used, and results were confirmed with Treponema pallidum Haemagglutination Assay (TPHA) kit. Of these 400 women, 3(0.75%) was confirmed positive. The percentage sero-positivity varies across the three senatorial districts, 1.3% was reported in the urban central district, 0.83% in the north and none (0%) was seen in the southern district. The mean age of the women is 31 years, meaning that they are still within the sexually active age bracket. More efforts in public enlightenment will help in the control of STIs in Ondo State.